Design and Clinical Evaluation of a Womb Sound Simulator Device for Reducing Stress in Preterm Infants in the Neonatal Intensive Care Unit (NICU) (Development Engineering Conferences Center Articles Database, 2025)
Preterm infants face significant physiological and developmental challenges due to the stressful environment of the Neonatal Intensive Care Unit (NICU), which starkly contrasts with the sensory-rich uterine environment. This abrupt transition can negatively impact neurodevelopmental outcomes. To address this, we propose the design of an innovative womb sound simulator. This device aims to recreate the auditory environment of the womb by using a multi-speaker system that generates directional sounds, including the maternal heartbeat, amniotic fluid noises, and live parental voice transmission via a SIM800L module. The primary objective is to reduce stress in preterm infants, thereby improving physiological stability and promoting better developmental care. Although the device has not yet been built, this paper presents its conceptual design, technical architecture, and a detailed protocol for its future clinical evaluation. The proposed study will be a randomized controlled trial (RCT) assessing physiological (heart rate, blood oxygen) and behavioral (NISS, PIPP-R scales) stress indicators. This technology holds the potential to bridge a critical gap in neonatal care by providing a non-invasive, developmentally supportive intervention.